An Empirical Investigation on Credit Card Repayment Pattern of Academicians in Malaysia - Kuah, Yoke Chin; Wei, Chooi Yi; Chin, Lai Kwan; Chia, Mei Si (UUM Press, 2017)
The credit card market has witnessed tremendous growth resulting from a paradigm shift in technology. The genuine usage of credit cards as a form of convenience has diverged to overspending, irresponsibility, revolving liability and bankruptcy. This implies that possession of credit cards has brought about a change in users repayment behavior. Thus, this study aims to determine academicians credit card repayment pattern in a private tertiary institution in Malaysia. The dependent variable is the repayment pattern and the independent variables that serve as the attributes include personal attitude and spending pattern, while gender and parenthood serve as the moderating variables. Findings revealed that personal attitude and spending pattern were important attributes in determining the repayment pattern among the academicians. Gender and parenthood were found to play a moderating role in the repayment pattern. Findings from this study is expected to facilitate the government and credit card companies to work towards nurturing a financially healthier and informed society, and also to each out positively to the younger generations through the influence of the academicians.